Oil/water separation by super-hydrophobic wastepaper cellulose-candelilla wax cryogel: a circular material-based alternative - Romero-Montero, A.; Rosas-Melendez, S. A.; Valencia-Bermúdez, J. L.; Nuñez-Tapia, I.; Piña-Barba, M. C.; Melgoza-Ramírez, L. J.; Leyva-Gómez, G.; Del Prado-Audelo, M. L. (Frontiers in Materials, 2023)
Introduction: One of the most attractive fields for cellulose aerogels is water remediation, basically in the pollutant’s adsorption and oil/water separation. There are different sources to extract cellulose, but the extraction from paper waste is an excellent option for impulse circular materials applications. Methods: We obtained cellulose from office waste paper through a simple alkali method and used it to fabricate an aerogel by freeze-drying based on the materials’ circularity. To increase lipophilicity, the aerogel was modified using two different coatings: polycaprolactone (WOPP) and candelilla wax (WOPW), extracted from a Mexican plant. The aerogels were analyzed by several physicochemical techniques such as Scanning Electronic Microscopy, Infrared spectroscopy, and thermal analysis. Results and Discussion: To our knowledge, this is the first time that candelilla wax has been reported as aerogel modification. The highly porous aerogels showed a density of around 0.1 g/cm3 and a fibrous structure. Furthermore, the contact angle of the aerogels was measured to compare the hydrophobicity of the surfaces, showing values around 120° in the modified aerogels compared with the hydrophilic behavior of pristine cellulose aerogel. The achieved recycled mineral oil absorption capacity for WOPW was 6.1 g/g, while for WOPP was 4.88 g/g. Thus, we obtained a natural coating aerogel with a high water/oil separation potential.